THE INTERCULTURAL DIMENSION IN ENGLISH LANGUAGE TEACHING: VIETNAMESE UNIVERSITY ENGLISH TEACHERS’ VOICES - Nguyen, Lan Thi Thuy; Biebricher, Christine; Ward, Gillian (VNU Journal of Foreign Studies; Vol 37 No 6, 2021)
In recent decades, there has been increasing interest in implementing the intercultural dimension (ID) in foreign language teaching to enhance students’ intercultural communicative competence (ICC), the capability to interact across linguistic and cultural boundaries. This article reports on a study that examines the English language teaching (ELT) of two Vietnamese university English teachers (VUETs) to investigate if and how they implemented the ID in their teaching. Situating the study within a qualitative case study approach, we collected data from interviews, classroom observations, and documents. Findings of this study show that these two teachers have not yet fully implemented the ID in their lessons. More specifically, they could transmit intercultural knowledge to their students; however, they could not develop their students’ intercultural attitudes, skills, or awareness. When providing cultural knowledge, they primarily relied on the prescribed textbooks’ cultural content and their understanding. The article sheds light on influential factors for VUETs’ ELT practices and offers implications for enhancing Vietnamese students’ ICC.